2018
DOI: 10.21273/hortsci12739-17
|View full text |Cite
|
Sign up to set email alerts
|

Partitioning of Dry Matter into Fruit Explains Cultivar Differences in Vigor in Young Olive (Olea europaea L.) Trees

Abstract: Low vigor and early and abundant production are desirable traits for modern tree crops. In olive, most cultivars are too vigorous and cannot be successfully constrained in the small volume allowed by the straddle harvester used in the so-called superhigh-density (SHD) orchards. Only few cultivars appear to have sufficiently low vigor to be suitable for this system. These cultivars combine low vigor with earlier and higher yield. This study investigated the hypothesis that differences in vigor between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
4
10
1
Order By: Relevance
“…Increments in TCSA (and thus for whole-tree biomass) were lower for fruiting than non-fruiting treatments ( Figure 2 A and Figure 3 ), in line with previous findings in olive trees ( Fernández et al., 2015 ; Rosati et al., 2018a ). The TCSA of Arbequina NF was comparable to that of Frantoio NF up to the first three years of observation, confirming that the low vigor generally observed in Arbequina is due to its early and abundant fruiting (up to 159 g of fruit + flower dry matter per tree in the first and second year after transplanting Rosati et al., 2018a ; 2018b ). In the fourth year, however, the TCSA in Frantoio NF was significantly greater than that of Arbequina NF ( Figure 2 A).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Increments in TCSA (and thus for whole-tree biomass) were lower for fruiting than non-fruiting treatments ( Figure 2 A and Figure 3 ), in line with previous findings in olive trees ( Fernández et al., 2015 ; Rosati et al., 2018a ). The TCSA of Arbequina NF was comparable to that of Frantoio NF up to the first three years of observation, confirming that the low vigor generally observed in Arbequina is due to its early and abundant fruiting (up to 159 g of fruit + flower dry matter per tree in the first and second year after transplanting Rosati et al., 2018a ; 2018b ). In the fourth year, however, the TCSA in Frantoio NF was significantly greater than that of Arbequina NF ( Figure 2 A).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, it has been found that deflowering resulted in strong increments in vegetative growth also in young olive trees, and that this eliminated differences in vigor (i.e. vegetative growth) between plants of the cultivar Arbequina (low vigor) and those of the cultivar Frantoio (high vigor), suggesting that cultivar differences in vigor may be explained in terms of different dry matter partitioning towards fruit (Rosati et al, 2017(Rosati et al, , 2018a. This demonstrated that competition for resources plays a major role in determining tree growth in young olive trees, suggesting that tree growth is source limited (Rosati et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%
“…The branching habit is one of the main factors affecting carbon partitioning between wood and leaves. Low-vigor and highbranching genotypes of the SILVOLIVE collection have a higher number of nodes and leaves (R 2 = 0.7), which means increased canopy density and may determine higher number of potential fruiting sites, becoming an important trait to be used to produce and export more assimilates toward fruits (Rosati et al, 2018). Otherwise, the hexaploid MAR1 and MAR3, together with most FRA and AMS genotypes show high apical growth with a low number of secondary stems.…”
Section: Phenotypic Diversity Of the Silvolive Collectionmentioning
confidence: 99%
“…Convincing evidence has been provided that these traits are genetically encoded by the root portion of the grafted plant, playing the rootstock genotype essential roles in shaping variation of these traits in the scion (Warschefsky et al, 2016). In addition, rootstocks can also affect the branching pattern of the scion (Costes et al, 2010) and promote early and more abundant bearing in young olive trees (Rosati et al, 2017(Rosati et al, , 2018. On the one hand, we have verified that all subspecies can be grafted with commercial olive varieties, including cuspidata, which has the maximum genetic distance with europaea ( Supplementary Table S9).…”
Section: Silvolive a Germplasm Collection For The Identification Of mentioning
confidence: 99%
“…Notwithstanding, in stone fruit trees, the presence of an elevated number of fruits alters the source-sink balance, by increasing assimilate accumulation into the fruits and/or by inducing an intensification of competition among them and between vegetative and reproductive growth (Morandi et al, 2008;Costa et al, 2018). This is also the case in olive (Rosati et al, 2017(Rosati et al, , 2018b. As a rule, high crop loads cause a decrease in tree growth (Intrigliolo and Castel, 2009), mainly during the last phases of fruit development (Intrigliolo et al, 2014).…”
Section: Competition Among Sinksmentioning
confidence: 75%